Stylistic analysis on Douglas Malloch’s “Be the Best of Whatever You Are” poem - Ihsan Tanama Sitio; Rahmadsyah Rangkuti (Universitas Islam Sultan Agung, 2023)
The current study aims to analyze the stylistic devices and describe their realization in constructing the theme and meaning in Douglas Malloch’s “Be the Best of Whatever You Are” poem. This descriptive qualitative study applied critical content analysis as an approach. Leech & Short’s (2007) stylistic theory was adopted as an analytical tool to examine the levels of language (style) in the poem. Based on the findings, there are 67 items found in the phonological level, 60 items found in the graphological level, 7 items found in the morphological level, 151 items found in the lexical levels, 30 items found in the syntax level, and lastly, there are 13 items found in the semantic level. The stylistic realization has revealed that Malloch uses varied linguistic elements in constructing the theme of this particular poem. Importantly, Malloch, through this poem, conveys a message of hope and motivation for people of all ages to always remember that a complex reality and negative aspects in life can be juxtaposed with the positive ones such as being the best version of ourselves and share it to the world.